Zasady aktualizacji wartości zapasów - Gos, Waldemar (The Rules of Stock Revaluation, 2005)
"The purpose of this article is to present reasons which cause decisions of revaluating stock, namely:- losing control over stock,- impairment in use value or exchange value of stock."
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 239-248